2008
DOI: 10.1186/1472-6963-8-269
|View full text |Cite
|
Sign up to set email alerts
|

In-reach specialist nursing teams for residential care homes: uptake of services, impact on care provision and cost-effectiveness

Abstract: Background: A joint NHS-Local Authority initiative in England designed to provide a dedicated nursing and physiotherapy in-reach team (IRT) to four residential care homes has been evaluated. The IRT supported 131 residents and maintained 15 'virtual' beds for specialist nursing in these care homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 59 publications
1
51
0
4
Order By: Relevance
“…Alternative approaches include specialist in-reach teams to support care-home staff, which have been associated with reductions in admission to hospital through provision of care at the care home. 30 None of our case vignettes included the use of advancecare planning, reflecting the cases they were derived from. However, targeted advance-care-planning interventions reduce admissions to hospital among care-home residents and were associated with reductions in mortality in one study.…”
Section: Themes Common To Various Scenariosmentioning
confidence: 99%
“…Alternative approaches include specialist in-reach teams to support care-home staff, which have been associated with reductions in admission to hospital through provision of care at the care home. 30 None of our case vignettes included the use of advancecare planning, reflecting the cases they were derived from. However, targeted advance-care-planning interventions reduce admissions to hospital among care-home residents and were associated with reductions in mortality in one study.…”
Section: Themes Common To Various Scenariosmentioning
confidence: 99%
“…45 For residents in care homes who are not close to death, specialist in-reach nursing teams in the UK have been employed to try to avert hospital admissions. 50 An evaluation of the impact of the nursing team in four residential homes included the convening of an expert panel, who judged that 197 admissions were avoided for 131 residents. However, the cost savings from the intervention were only modest, which may limit its wider adoption.…”
Section: Transitions For Care-home Residentsmentioning
confidence: 99%
“…16 Also, the home care reduces the number of hospitalizations and the costs associated with them, reducing the demand for tertiary healthcare services. [17][18][19] However, for a quality care at home, it is necessary that the individual and the family are prepared to assume the responsibility for the care. Some studies emphasized that the family members often perform the care with knowledge and skill acquired with right or wrong experiences and the healthcare team has been negligent about the guidance on what the patient and the family need.…”
Section: Home Carementioning
confidence: 99%
“…13 A new home care service proposed in a study, which visits more often, has shown that this continuous follow-up allows to identify, at a significantly higher level, the nursing care needs, beyond the identified by the existing nursing services. 17 Among the nursing actions identified by the subjects, those related to affective level, such as attention and affection in how they feel cared for, stood out. 20 However, sometimes the patient is surrounded by stigma with this care, because the receptivity and expectations.…”
mentioning
confidence: 99%